2016
DOI: 10.1002/maco.201609102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multipass TIG welding on the corrosion resistance and microstructure of a super duplex stainless steel

Abstract: This is a study of the effect of repetitive TIG (tungsten inert gas) welding passes, melting and remelting the same material volume on microstructure and corrosion resistance of 2507 (EN 1.4410) super duplex stainless steel. One to four weld passes were autogenously (no filler added) applied on a plate using two different arc energies and with pure argon shielding gas. Sensitization testing showed that multipass remelting resulted in significant loss of corrosion resistance of the weld metal, in base material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
(37 reference statements)
2
24
0
5
Order By: Relevance
“…Nilsson et al [11] investigated the precipitation of secondary phases in different SDSS weld metals, for a selection of times and temperatures. Hosseini et al [12,13] performed multipass TIG remelting to study the precipitation of sigma phase in the heat-affected zone of a wrought SDSS alloy; however, the weld metal was not studied and the thermal cycles did not allow for studies of effects of longer heat treatments. In particular, the precipitation temperature and morphology of deleterious secondary phases need further research.…”
Section: Recommended For Publication By Commission IX -Behaviour Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Nilsson et al [11] investigated the precipitation of secondary phases in different SDSS weld metals, for a selection of times and temperatures. Hosseini et al [12,13] performed multipass TIG remelting to study the precipitation of sigma phase in the heat-affected zone of a wrought SDSS alloy; however, the weld metal was not studied and the thermal cycles did not allow for studies of effects of longer heat treatments. In particular, the precipitation temperature and morphology of deleterious secondary phases need further research.…”
Section: Recommended For Publication By Commission IX -Behaviour Of Mmentioning
confidence: 99%
“…The sensitization of duplex stainless steels is due to the low Cr and Mo contents in regions adjacent to intermetallics and nitrides and also sometimes the formation of secondary austenite with low Cr and N [12]. Sensitization testing was performed based on ASTM A262 [19], Practice A with some modification.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Similar observations were reported by Magnabosco et al [29], where both Cr- and Mo-depleted metastable δ were attacked at the earlier aging stage. Hosseini et al [25] also observed the sensitization of δ in the vicinity of small σ particles in multiply reheated 2507 SDSS. Similarly, even 15 h of aging time at 675 °C did not heal the Cr-depleted region in 2205 DSS [43].…”
Section: Discussionmentioning
confidence: 96%
“…Sensitization screening testing was performed by electrolytically etching the cross-section in 7% oxalic acid, applying 2 V for 30 s, inspired by ASTM A262 Practice A [24], and similar to the procedure used by Hosseini et al [25]. The reason for using a low acid concentration and short etching time was to find the regions most susceptible to local corrosion attack.…”
Section: Methodsmentioning
confidence: 99%
“…During heating, the austenite phase is solubilized and subsequently precipitated during the cooling. Due to the fast cooling rate, the formation of austenite is impaired in the HAZ, causing excessive ferritization and coarse granulation when compared with the solubilized BM . The fast cooling of the HAZ also influences the diffusion and redistribution of alloying elements in the two phases, changing its PREN and its corrosion resistance .…”
Section: Introductionmentioning
confidence: 99%